Zinc Deficiency in Type II Diabetes Mellitus: Zinc Deficiency and Diabetes - Javaid, Muhammad Faisal; Rasheed, Saima; Siddiqui, Rafiq Ahmad; Habib, Bilal; Chaudhry, Erum Rashid; Rashid, Anam Abdul (Pakistan Journal of Health Sciences, 2024)
Zinc (Zn) is an essential trace element for various biochemical, physiological and immunological functions in the human body. Zn deficiency affects up to 25% of the population in poor countries and up to 15% in industrialized countries. Diabetes Mellitus (DM) refers to impaired glucose metabolism, which leads to a constellation of disorders and is marked by poor immunity in the diseased subject. Zn deficiency has an inverse relationship with glycemic control. Objective: To assess the serum Zn level in diabetic patients in comparison with healthy subjects. Method: A cross sectional study was conducted at Department of Biochemistry, Niazi Welfare Foundation Teaching Hospital, Sargodha, Pakistan from 1st June, 2023 to 31st December, 2023. Data were collected after institutional review board (IRB) approval (NM&DC-IRB-53; Dated 1st Dec, 2022) and informed consent was taken from all the participants. A total of 150 participants were equally divided into two groups based on glycemic control. Serum Zn levels of all participants were estimated via atomic absorption spectrophotometry. Descriptive statistic was used to calculate mean and standard deviation on SPSS version 23.0. Results: The mean value of serum Zn level was significantly lower (8.83 ± 1.64 µmol/L) in diabetic subjects as compared to healthy participants (18.63 ± 6.13 µmol/L). Conclusions: Deficiency of serum Zn level has a negative relationship with the body’s glycemic control.